The reception history of Esther a genderqueer/non-binary reading of the ancient texts and in modern scholarship - Thompson, H (2021)
The Book of Esther has been regarded by some critics as displaying unusual gender roles for a biblical text, particularly because there appear to be some gender role reversals or gender ambiguities occurring in the text. Modern reception of Esther can be broadly grouped into two categories: characters in the text are interpreted in a cisnormative manner, or some characters are interpreted as being subversive. Both groups of scholarship are problematic for non-binary/genderqueer readers in different ways, and this thesis aims to take a non-binary/genderqueer approach to Esther to assess if this text has the capacity to be read in a manner free from the gender binary.